2018
DOI: 10.1016/j.dhjo.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of anxiety and depression symptoms after a lower limb amputation

Abstract: Tailored multidisciplinary interventions need to be developed providing support before and after an amputation surgery, in order to reduce anxiety and depression symptoms and promote psychological adjustment to limb loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 51 publications
1
26
1
3
Order By: Relevance
“…Pain is a well-known predictor of depression and anxiety in patients with diabetic foot and has a deleterious effect on postoperative wound healing and usually contributes to delayed wound healing in patients experiencing elevated levels of anxiety. 49 Strong evidence suggests that with time, the patient copes better with his or her situation and sees his or her level of anxiety dropping down to an acceptable level. 48,49 Findings have also shown that health care providers without psychological or psychiatric training often fail to diagnose or to adequately address clinical depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain is a well-known predictor of depression and anxiety in patients with diabetic foot and has a deleterious effect on postoperative wound healing and usually contributes to delayed wound healing in patients experiencing elevated levels of anxiety. 49 Strong evidence suggests that with time, the patient copes better with his or her situation and sees his or her level of anxiety dropping down to an acceptable level. 48,49 Findings have also shown that health care providers without psychological or psychiatric training often fail to diagnose or to adequately address clinical depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…49 Strong evidence suggests that with time, the patient copes better with his or her situation and sees his or her level of anxiety dropping down to an acceptable level. 48,49 Findings have also shown that health care providers without psychological or psychiatric training often fail to diagnose or to adequately address clinical depression and anxiety. 50 In the context of the collaborative care model, which is composed of a multidisciplinary team, during the rehabilitation process, health care professionals are more likely aware that patients may experience these symptoms which may be confused with diabetes symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigating emotional response to surgery have demonstrated an elevated risk of anxiety and depression before surgery, followed by a signi cant decrease thereafter. This phenomenon was described amongst patients subjected to emergency and major elective surgeries, including RC [6,8]. In our study more than one third of patients who were scheduled to RC had anxiety and depression symptoms within the mild to severe range (HADS score ≥ 8).…”
Section: Discussionmentioning
confidence: 56%
“…The incidence of angina pectoris and heart failure was higher in their study, but they showed a substantial mortality after revascularization (29). A recent study regarding the incidence of anxiety or depression amongst persons after a LLA, due to diabetes, showed even higher incidences of anxiety or depression (30). For future research, we recommend a standardized description of comorbid conditions in studies of persons with a LLA.…”
Section: Prevalence Of Comorbiditymentioning
confidence: 86%